Achieving high-quality silver sintered joint for highly-reliable schottky barrier diodes via pressureless method - Dai, Chenyi; Wang, Yong; Lin, Pengrong; Hao, Zilin; Wang, Chaoyang; Feng, Xiaocheng; Liu, Xueming (Frontiers in Materials, 2023)
The fabrication of silver joints was done using the pressureless sintering techno logy to suit the demand of high-reliability schottky barrier diodes (SBD). Porosity of 10.6% and shear strength of 39.6 MPa were reached under the optimized parameters of 290℃ sintering temperature and 40 min residence time. The sintered joint demonstrated good mechanical/thermal/electrical performance in the ultimate reliability assessment testing, including the temperature cycling test, second sintering test, steady-state lifetime test, and intermittent lifetime test. This study demonstrated the viability of pressureless sintering of silver joints with good high-temperature reliability, which has significant application potential for aeronautical high-reliability power electronics.